The Influence of Vegetation Cover on the Settlement Behavior of Permafrost Subgrade in the Greater Khingan Mountains Forest Region - Zhibo Xu; Guihe Wang; Wu Chen (Applied Sciences, 2023)
The subgrade construction in the permafrost forest region will aggravate the degradation of frozen soil, which will lead to the settlement of the subgrade. Based on the road project of National Highway 332 in the Great Khingan Mountains, by means of field observation, experimental testing, and numerical simulation, a thermo-hydro-mechanical coupling numerical model of the permafrost subgrade considering vegetation cover was established to analyze the influence of vegetation cover on the settlement behavior of the permafrost subgrade. The study indicates that vegetation cover mainly influences the seasonal active layer temperature of permafrost, and its cooling effect on permafrost in the warm season is more significant compared with the warming effect in the cold season. The volumetric water content of the subgrade with vegetation cover is greater than that without vegetation cover in the cold season. The situation is just the opposite in the warm season. The damage to the subgrade is mainly reflected in the settlement caused by the thawing of frozen soil. The maximum settlement of the subgrade with and without vegetation cover is 8.3 mm and 9.5 mm at the foot of the subgrade slope. After construction, the settlement behavior of the permafrost subgrade will undergo a degradation period of 3 years, a restoration period of 2 years, and finally, tend to be stable.